New oral anticoagulants for stroke prevention in atrial fibrillation: impact of study design, double counting and unexpected findings on interpretation of study results and conclusions - Chan, Noel C.; Paikin, Jeremy S.; Hirsh, Jack; Lauw, Mandy N.; Eikelboom, John W.; Ginsberg, Jeffrey S. (Thrombosis and Haemostasis, 2014)
Four recently introduced new oral anticoagulants (dabigatran, rivaroxaban, apixaban and edoxaban) have been shown to be at least as efficacious and safe as warfarin for stroke prevention in patients with atrial fibrillation in their respective trials. The first three have been approved, while edoxaban is awaiting regulatory approval. Several guidelines have endorsed the approved new oral anticoagulants over warfarin because of their favourable risk-benefit ratio, low propensity for food and drug interactions, and lack of requirement for routine coagulation monitoring. In this invited review, we summarise the results of the four studies and discuss widely held conclusions. We take a step further and discuss how differences in study design, analysis plan, and unexpected events affect the interpretation of the study results. Finally, we take our re-interpretation of study results and discuss how they might impact clinical practice and anticoagulant choice for patients.
Keywords: Clinical trials; oral anticoagulants; stroke / prevention; thrombosis